Effectiveness of High Reflective Roofs in Minimizing Energy Consumption in Residential Buildings in Iraq. (2015) - Mohamed, Haider; Chang, Jae D.; Alshayeb, Mohammed
Abstract: Residential buildings in Iraq consume 48% of the country's total electricity production. As residential air-conditioning usage increases, so does the demand on the country's electrical power infrastructure resulting in more frequent power cuts and rolling blackouts. This paper investigates the effectiveness of applying high reflective roofs to reduce the cooling loads of Iraqi houses and in turn electricity demand. Previous studies have shown high reflective roofs are capable of reducing cooling loads by about 45% compared to typical roof finishes for various climates. However, there are insufficient data for very hot and dry climates like that of Iraq. Findings from this study's preliminary energy simulations indicate that high reflective roofs can provide a significant reduction in cooling loads compared to the typical roof finishes of Iraqi houses therefore potentially reducing the energy demand on the country's energy infrastructure.